Exploiting CRISPR/Cas system in controlling antibiotic resistance of bacteria - Pourya Gholizadeh; Elnaz Faghfuri; Khudaverdi Ganbarov; Hossein Samadi Kafil (BioSocial Health Journal)
The emergence and spread of antimicrobial resistance is a threat to human health, therefore there is a need to explore new strategies to combat antibiotic-resistant bacteria. Antimicrobial resistance genes are mainly transmitted through horizontal gene transfer (HGT) mediated by transposable elements, phages, and plasmids, which leads to the emergence of multidrug-resistant bacteria. Clustered Regularly interspaced Short Palindromic Repeats (CRISPR) and CRISPR-associated proteins (Cas) protect archaebacteria and eubacteria from potentially harmful foreign DNA such as plasmids, transposable elements, and phages. Several studies have introduced the CRISPR/Cas system as an innovative and effective strategy to trigger antibiotic resistance and virulent genes in bacteria. Therefore, this study aimed to introduce the CRISPR-Cas system in controlling antibiotic resistance of bacteria. We hope exploiting CRISPR/Cas could provide a bright future for the treatment of disastrous infections with resistant and virulent organisms.